Impact of cutoff points on adolescent sedentary behavior measured by accelerometer - Moura, Rally Rayssa Dias (2019)
The aim of this study was to analyze the impact of cutoff points in defining sedentary behavior (SB) time and prevalence, measured by accelerometers in adolescents from Northeastern Brazil. This is a cross-sectional study with adolescents aged between 10 and 14 years from public schools in João Pessoa, Paraíba state, conducted in 2014. SB was measured by an accelerometer (ActiGraph GT3X+) and the following cutoff points were applied: Evenson (≤ 25 counts/15sec), Puyau (< 800 counts/60sec), Vanhelst (≤ 400 counts/60sec), Hänggi (< 3 counts/1sec) and Romanzini (≤ 180 counts/15sec), along with the 20 and 60-minute accelerometer nonwear time. To compare the average and prevalence of excessive SB time (≥ 8 hours/day) between cutoff points, one-way ANOVA for repeated measures (Bonferroni post hoc) and the Cochran test, respectively, were used. There were significant differences in average SB between the cutoff points analyzed (p > 0.05), ranging from 37.44 min/day (Romanzini: 547.37 min/day vs. Vanhelst: 584.81 min/day) to 370.44 min/day (Hänggi: 310.51 min/day vs. Puyau: 680.95 min/day) for the 20-minute nonwear criterion; and from 81.52 min/day (Evenson: 502.41 min/day vs. Romanzini: 583.93 min/day) to 361.94 min/day (Hänggi: 354.58 min/day vs. Puyau: 716.52 min/day) for the 60-minute criterion. The prevalence of excessive SB varied from 3.3% (Hänggi) to 99.3% (Puyau). Average daily SB and the prevalence of excessive SB in the adolescents showed marked differences between the cutoff points assessed.